2022
DOI: 10.1093/bjsw/bcab255
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the social gradient in children’s social care

Abstract: The social gradient in children’s social care refers to the relationship between socio-economic status and the likelihood of a child welfare intervention. This article reports on a quantitative study of national administrative data, aiming to identify social gradients across all local authorities in England and to examine the factors affecting their relative strength. An anonymised extract of case-level information on all school-aged children involved with statutory social care services in 2018–2019 was combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Research on children in care in the UK on a voluntary and compulsory basis by Bywaters and colleagues (Bywaters et al, 2016(Bywaters et al, , 2018Webb, Bywaters, Elliott, & Scourfield, 2020;, used aggregate data on looked after children (CLA)and confirmed associations between area deprivation and higher rates of children in care. Goldacre and Hood (2022) found higher rates of children in care from deprived households in affluent rural areas, which is supported by earlier work .…”
Section: Background Literature and Study Rationalesupporting
confidence: 80%
“…Research on children in care in the UK on a voluntary and compulsory basis by Bywaters and colleagues (Bywaters et al, 2016(Bywaters et al, , 2018Webb, Bywaters, Elliott, & Scourfield, 2020;, used aggregate data on looked after children (CLA)and confirmed associations between area deprivation and higher rates of children in care. Goldacre and Hood (2022) found higher rates of children in care from deprived households in affluent rural areas, which is supported by earlier work .…”
Section: Background Literature and Study Rationalesupporting
confidence: 80%
“…The second theme was social integration which was a consolidation of four different organizers (level 2) as displayed in Table 4 . Experts ( 1 , 9 , and 11 ) said “the acceptance of the social norms, avoiding of breaking the law, and committed to obey the rules are effective in social health; social health is necessary for the health of the members of the society”. Experts 3 to 7 expressed: “family making is the cause of social health”.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, professionals should particularly consider the differences in social and economic factors and their impact on individuals’ health in emergency health conditions [ 10 ]; so that the disadvantaged population does not endure a heavier burden of health emergency as for example pandemics. It should be noted that people from low socioeconomic backgrounds experience worse health conditions and shorter lifespans than those counterparts from higher socioeconomic backgrounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, at an area level, there is increasing evidence that both deprivation and within-area inequality are associated with child welfare interventions. Some of these studies are based on England only (Bennett et al , 2020; Goldacre and Hood, 2022; Webb et al , 2020), but Webb et al (2021) also included Wales and found no significant difference between the countries.…”
Section: Introductionmentioning
confidence: 99%